Iot-Based Patient Health Monitoring System - Mr. Rajesh; Hemanathan T; Muniappan K; Naveen B; Sasi Kumar P (Journal of Advanced Zoology, 2024)
The emergence of the Internet of Things (IoT) has revolutionized healthcare by enabling remote patient monitoring systems. This system utilizes wearable sensors to collect vital signs such as heart rate, blood glucose level and body temperature. If the patient’s temperature increases above 100 degrees Celsius then the alarm will be generated. The collected data is transmitted wirelessly to a secure cloud platform for real-time analysis and visualization. This allows Doctors to remotely monitor patients’ health conditions, intervene promptly in case of emergencies, and improve overall care quality.